2012
DOI: 10.1007/s12185-012-1240-5
|View full text |Cite
|
Sign up to set email alerts
|

XCIND as a genetic disease of X-irradiation hypersensitivity and cancer susceptibility

Abstract: The XCIND syndrome is named after distinct hypersensitivity to ionizing (X-ray) irradiation, cancer susceptibility, immunodeficiency, neurological abnormality, and double-strand DNA breakage. The disorders comprising XCIND syndrome are usually inherited in an autosomal recessive manner. Ataxia telangiectasia (A-T) is one such disease, and is caused by biallelic germline mutation of the Ataxia telangiectasia mutated (ATM) gene. Heterozygous carriers of the ATM mutation, who do not show A-T-like clinical symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…More than twenty molecules are involved in the V(D) J recombination and CSR; and inability to persecute the programmed DDR results in primary immunodeficiency (PID) ( Table 1) [3,6,[8][9][10][11][12][13][14][15]. The patients with defect either in DNA damage signal or in NHEJ process present PID phenotype, and often show one or more of phenotypes that include radiosensitivity, predisposition to malignancy, developmental delay, and neurological deficits ( Table 2).…”
Section: Dna Damage Repair Networkmentioning
confidence: 99%
“…More than twenty molecules are involved in the V(D) J recombination and CSR; and inability to persecute the programmed DDR results in primary immunodeficiency (PID) ( Table 1) [3,6,[8][9][10][11][12][13][14][15]. The patients with defect either in DNA damage signal or in NHEJ process present PID phenotype, and often show one or more of phenotypes that include radiosensitivity, predisposition to malignancy, developmental delay, and neurological deficits ( Table 2).…”
Section: Dna Damage Repair Networkmentioning
confidence: 99%
“…Inability to persecute the programmed DDR and repair results in the developmental disorder in T, B cells, that is, primary immunodeficiency (PID). These PID patients often show one or more of phenotypes that include radiosensitivity, predisposition to malignancy, developmental delay, or neurological deficits such as microcephaly, which has been called XCIND [1]. These disorders provide us with an insight into physiological importance and function of each molecule in health and disease.…”
Section: Dr T Morio Focused On Primary Immunodeficiency (Pid) V(d)mentioning
confidence: 99%
“…Ataxia-telangiectasia (A-T [MIM 607585]) is a rare autosomal-recessive disorder characterised by hyper-radiosensitivity, cancer predisposition, immunodeficiency and neurodegeneration 9 . A-T is caused by germline mutations in the ataxia-telangiectasia mutated ( ATM ) gene encoding ATM kinase, which is a DSB damage response master kinase member of the evolutionarily conserved phosphatidylinositol-3-kinase-related kinase (PIKK) family 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiological studies demonstrated that A-T heterozygous carriers showed a several-fold increased risk of breast and ovarian cancers in comparison with normal individuals 11 . Since A-T heterozygous carriers, who are clinically asymptomatic, exist at a rate of approximately 1% in human populations 9 , we assume that the heterozygous form of recessive mutations associated with hyper-radiosensitive genetic disorders such as A-T when in a homozygous state might be a genetic determinant of individual differences in healthy human populations. Previous studies indicated that most primary cells from A-T heterozygous carriers were more radiosensitive than those from normal individuals 12 , while it was also reported that the radiosensitivities of A-T heterozygous carriers and normal individuals were not segregated because of the genetic heterogeneity in some cases 13 .…”
Section: Introductionmentioning
confidence: 99%